A comunicabilidade nas peças dodecafônicas para flauta e piano de César Guerra Peixe - Fabio Henrique Viana (2005)
This study is an analysis of two twelve-tone pieces Música (1944) and Allegretto con moto (1945) for flute and piano, composed by the Brazilian composer César Guerra Peixe. Its aim is to identify the presence of elements of communicability, as it was defined by the composer in his Memorial. The pieces are structured, mainly,through the repetition of motifs and arguments as well as the relief/tension dualism. These devices are employed in a tonally-oriented way. The dimension of sections and parts and the location of climactic points follow, approximately, the Golden Section. Rhythm receives a pointillistic treatment. The twelve-tone row is used in an unorthodox way and there is recurrence of pitch-class sets which are either fragments of the twelve-tone row or diatonic formations. In these pieces, the communicability occurs through the combination of tonal and atonal idioms.